Diagnostic comparison of ultrasonography, hysteroscopy and histopathology in abnormal uterine bleeding - Raut, Srushti Sunil; Babbar, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The objective of the study was to do diagnostic comparison of ultrasonography, hysteroscopy and histopathological examination in evaluation of abnormal uterine bleeding. Methods: An observational prospective study is conducted amongst 219 married women between age of 25 years to 59 years with Abnormal uterine bleeding admitted for diagnostic hysteroscopy at Obstetrics and Gynecology Department, Apollo Hospital, Bilaspur, Chhattisgarh from November 2022 to October 2023. Statistical analysis was assessed by chi square test. Results: Myoma is best diagnosed by Sonography. The exact size, shape, type of fibroid and location can be accurately diagnosed by USG. Endometrial hyperplasia, endometrial polyp, submucous fibroid, growth, septum, flimsy adhesions, focal lesions and intracavitary intrauterine lesions are best diagnosed by hysteroscopy. Endometrial carcinoma is best diagnosed by histopathology. Conclusions: Hysteroscopy has important role in diagnosis of intrauterine and endocervical canal abnormalities. Addition of hysteroscopy with histopathological examination of endometrial and cervical biopsy sample along with transvaginal ultrasonography enhances the accuracy of diagnosis. Use of hysteroscopy, ultrasonography and histopathology were not competitive rather complementary for diagnosing patients with abnormal uterine bleeding. Diagnostic tools like ultrasonography, hysteroscopy and histopathology helps in accurate, early diagnosis of endometrial and cervical cancer which prevents further damage and further spread and metastasis of disease to adjacent tissues/ organs. Early diagnosis and cure increases life expectancy and decreases morbidity and mortality.